Enhanced Duration of Truffle Sauce Preservation due to Addition of Linoleic Acid - Bruno Tirillini; Filippo Maggi; Roberto Venanzoni; Paola Angelini (Journal of Food Quality)
Food products based on truffles such as truffle sauces are commonly sterilized by autoclaving. With the aim of reducing sterilization durations and temperatures and therefore minimizing the formation of new molecules while maintaining sterile conditions, natural molecules with bacteriostatic action can be added. This work takes into account molecular variations in a truffle sauce with linoleic and stearic acids added at various temperatures and durations of sterilization. As controls, the sterilized truffle sauces, not additives, were taken. The SPME/GC has always detected changes in the composition of the headspace but more significant at longer durations. An increase in temperature leads to the transformation of an important fraction of total alcohol into total aldehydes. Bacteriological tests were performed on total aerobic bacteria and Clostridium spp. The total bacterial load, even if low, is instead present in the controls for all temperature/duration combinations. Linoleic acid is more effective than stearic acid and contributes with a concentration of 10% (w/w) to a decisive reduction of the total bacterial load at 10′/121°C and 3′/130°C. The nutritional value of truffle sauces can be increased by adding nutraceuticals, and amongst these, linoleic acid could be a valid candidate.